Qualitative study exploring perceptions, attitudes and practices of adolescent university students in Lagos, Nigeria, towards a healthy lifestyle - Nnamdi C. Menakaya; Ifeoma N. Menakaya (AOSIS, 2022)
Background: Lifestyle behaviours such as physical activity, dietary habits and sedentary behaviour are developed and established during adolescent years. Aim: This study aimed to explore the perceptions, attitudes and practices of adolescent university students in Lagos, Nigeria, towards healthy lifestyle. Setting: Three university institutions in Lagos, Nigeria. Methods: Qualitative research design was employed. In-depth interviews (IDIs) using an audio-recorder were conducted with 18 adolescent university students recruited through purposive sampling from three university institutions in Lagos, Nigeria. Recorded interviews were transcribed verbatim and thematic content analysis was used to analyse transcribed data. Results: Study participants perceived a healthy lifestyle as balanced diet, regular physical activity and disease prevention. They described their attitudes and practices towards a healthy lifestyle in terms of personal conviction and disposition, regular physical activity and consumption of fruits and vegetables. Meal skipping and junk food consumption were notable unhealthy dietary practices. Home environment, school campus physical environment, peers, secondary school background and concerns about fast food quality were positive influences towards healthy lifestyle, while academic schedules, personal disposition school campus eateries and sociocultural background were negative influences. Computer and Internet activity was the main sedentary activity. Conclusion: Study participants' perception of healthy lifestyles in terms of balanced diet and physical activity aligned with the evidence-based guidelines for healthy lifestyle concepts. Regulatory policies and built environment that promote healthy dietary practices among adolescent university students are recommended. Contribution: Future research is suggested to examine the benefit of study participants' engagement in computer or Internet sedentary activities for academic activity and knowledge seeking towards healthy lifestyles.